2012
DOI: 10.3390/s120202018
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection of Naphthalene in Solvent Vapor Using a Functionalized PBG Refractive Index Sensor

Abstract: We report an optical refractive index sensor system based on a planar Bragg grating which is functionalized by substituted γ-cyclodextrin to determine low concentrations of naphthalene in solvent vapor. The sensor system exhibits a quasi-instantaneous shift of the Bragg wavelength and is therefore capable for online detection. The overall shift of the Bragg wavelength reveals a linear relationship to the analyte concentration with a gradient of 12.5 ± 1.5 pm/ppm. Due to the spectral resolution and repeatabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…However, we have recently shown that PLD deposited, porous WO3 performs similarly well on a MOS sensor platform [39]. In comparison to an optochemical naphthalene sensor described in [40], our sensor exhibits about 10 times longer response times (10 min vs. 1 min), but an at least 100 times lower detection limit (5 ppb vs. 500 ppb).…”
Section: Discussionmentioning
confidence: 75%
“…However, we have recently shown that PLD deposited, porous WO3 performs similarly well on a MOS sensor platform [39]. In comparison to an optochemical naphthalene sensor described in [40], our sensor exhibits about 10 times longer response times (10 min vs. 1 min), but an at least 100 times lower detection limit (5 ppb vs. 500 ppb).…”
Section: Discussionmentioning
confidence: 75%
“…By connecting a single mode (SM) fiber to the PBGs using UV curable glue, both gratings could be simultaneously monitored during the experiments. A detailed description of the fabrication process of the PBGs can be found elsewhere . Figure illustrates the structure of the planar sensor chip, including a cross‐section indicating the interaction of the evanescent field with a surrounding medium.…”
Section: Methodsmentioning
confidence: 99%
“…Such an optical device could be a Bragg grating sensor [12]. The field of application for such sensors includes temperature, pressure and strain sensing [12] or chemical analyses [13,14]. Previous works using conventional PMMA instead of hybrid polymers already proved that a change of the refractive index can be achieved by excimer laser irradiation of the polymer [15].…”
Section: Introductionmentioning
confidence: 99%